Cryopreservation Techniques for Ram Sperm - Amit Saha; Mohammad Asaduzzaman; Farida Yeasmin Bari (Veterinary Medicine International)
Germplasm storage and transportation in artificial insemination (AI) and other advanced technologies are facilitated by cryopreservation. In reproduction, the cryopreservation of sperm allows it to be transported across vast distances and used even after the sire’s death. However, the technique of cryopreservation might damage sperm and limit their activity. Several cryobiological investigations have reported that the integrity of the sperm membrane is frequently involved in the physical and biological elements that affect sperm survival at low temperatures during the cryopreservation process. However, successful cryopreservation of ram sperm is still a work in progress because a considerable percentage of sperm do not survive the freezing and thawing process. Sperms are destroyed during cryopreservation of semen due to varying concentrations of cryoprotective chemicals and if semen is not cooled at optimal cooling rates. Hence, it is crucial to know the optimum cooling rates with freezing and thawing protocols for maximum recovery of viable and functional sperm cells for a successful cryo-freezing of ram spermatozoa. Therefore, the current study compiled and compared the research on the impact of different cryopreservation procedures, cooling rates, equilibration time, and thawing protocols on post-thaw ram semen quality.